Perbedaan Paparan Debu Pada Pekerja Penggilingan Padi Pregolan Desa Jetis Kecamatan Kaliwungu Kabupaten Semarang Sebelum Dan Sesudah Pemasangan Local Exhaust Ventilation - - Ghaniysara; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
The rice milling process gives rise to variety of hazard. Hazard identification in the rice milling in Pregolan Desa Jetis Kecamatan Kaliwungu Kabupaten Semarang shows that there is chemical hazard in the form of grain dust that is included in organic dust. Dust is hazard that negatively affect number one in causing occupational disease. Disease arising due to organic dust, among others, organic dust toxicity syndrome, farmer lung and asthma. Preliminary research in the rice milling in Pregolan Desa Jetis Kecamatan Kaliwungu Kabupaten Semarang shows that the workers often feel uncomfortable and have difficulty breathing while working because of the grain dust. Therefore, the control needs to be done to reduce dust exposure, namely the installation of local exhaust ventilation. The purpose of this research is to analyze the differences of dust exposure to rice milling workers in Pregolan Desa Jetis Kecamatan Kaliwungu Kabupaten Semarang before and after the installation of local exhaust ventilation. This is an experimental research with one group pretest posttest design. The population in this research is measurement results of dust exposure to rice milling workers in Pregolan Desa Jetis Kecamatan Kaliwungu Kabupaten Semarang. The sample of this research is each four measurement results of dust exposure before and after the installation of local exhaust ventilation. Data analysis is conducted by comparing measurement results of dust exposure before and after the installation of local exhaust ventilation. The results showed that dust exposure after the installation of local exhaust ventilation dropped amounted to 0,5 mg/m3, 0,3 mg/m3 and 2,0 mg/m3. The conclusion is the installation of local exhaust ventilation in rice milling Pregolan Desa Jetis Kecamatan Kaliwungu Kabupaten Semarang can reduce the dust exposure